Pemanfaatan Limbah Jerami Padi dalam Pembuatan Edible Film (Kajian Penambahan Lignin dan Sorbitol) - Ringgo E. P. Putra; Cakrasena R. Santoso; Titi Susilowati (CV. Publikasi Indonesia, 2023)
Rice straw is a very abundant lignocellulose agricultural waste in Indonesia. This waste is generally used as much as 31% for animal feed, 7% for industrial purposes, and 62% burned in rice fields. This burning can cause respiratory disorders such as ARI and cancer. Lignocellulose itself is a polysaccharide consisting of lignin, cellulose, and hemicellulose. The lignin content in rice straw can be used for the production of edible film, so as to increase its usefulness and reduce the percentage of incineration of this waste in rice fields. Edible film is a thin layer made from edible materials and laid between food components. The main components constituting edible film are hydrocloids/lipids/composites, fillers, and plasticizers. The use of the addition of a plasticizing agent is to make edible film elastic. The use of this filler is to modify the edible nature of the film you want to produce. Examples of oligomeric substances and fillers are sorbitol and lignin. In this study, sorbitol and lignin materials were added to cellulose biomass materials derived from rice straw. These materials are stirred using a magnetic stirrer at a speed of 400 rpm and a temperature of 65oC for 25 minutes before the mixture is printed on a glass plate. After the edible film is printed and dried, an analysis of tensile strength and degradation of the edible film is carried out. The results showed a decrease in the tensile strength value of edible film with the lowest downward trend in the addition of 3% lignin lignin and 9 ml sorbitol. The results of the % degradation analysis show that the value of % degradation tends to increase without the addition of lignin.